Pengaruh Roti Fungsional Dadih terhadap Kenaikan Berat Badan Ibu Hamil di Padang, Indonesia: a Randomized Controlled Trial: The Impact of Dadih Functional Bread on Gestational Weight Gain for Pregnant Women in Padang, Indonesia: a Randomized Controlled Trial - Helmizar, Helmizar; Azrimaidaliza, Azrimaidaliza; Rusdi, Faza Yasira; Asrawati, Asrawati; Ferry, Ferdinal (Universitas Airlangga, 2025)
Background: Gestational Weight Gain (GWG) is correlated to the growth and development of foetus and pregnancy outcomes. Probiotics have a positive effect on gestational weight gain. Dadih is a traditional West Sumatra food containing 108 CFU/ml of probiotics. Objectives: This research aimed to investigate the effect of dadih functional bread on gestational weight gain. Methods: This research is a Randomised Controlled Trials (RCT) design with double blinds with a gestational age of 12-20 weeks belonging to 88 pregnant women. The tests for weight balancing scales were used. The data were examined using Independent T-test for difference test and General Liniar Model (GLM) repeated measures, and Analysis of Covariance (ANCOVA). Results: The average GWG was significantly 2 kg greater for the intervention group related to the control group (7.3±2.6 kg vs 5.4±3.8 kg). The GWG in the intervention group exceeded the recommended GWG per month. The results indicated that weight gain was difference across the four-time measurements in both groups. There was a significant different in the average GWG among the intervention control and the control group (p-value<0.001). Conclusions: Dadih functional bread supplementation for three months significantly effect the gestational weight gain. Thus, the consumption of the dadih products can be considered when planning the nutrition to advance the nutritional status of pregnant women.